Using the Kübler-Ross Model of Grief with Post-Traumatic Stress Disorder (PTSD): An Analysis of Manchester by the Sea - Rong-Rong Wang; Ya-huei Wang (Metathesis: Journal of English Language, Literature, and Teaching, 2021)
People may encounter different stages of grief during the course of bereavement, and not everyone can achieve a positive state of mind. This study intended to analyze how the characters in Manchester by the Sea, mainly Lee Chandler, Patrick Chandler, and Randi, manage their emotional responses when they are facing the loss of a loved one. The study used Elisabeth Kübler-Ross’s five-stage model of grief and post-traumatic stress disorder (PTSD) to analyze how these characters transition through their grief and whether they are likely to suffer from mental illness. Some people, like Randi and Patrick in the film, may recover from bereavement; however, some people, like Lee, may not, eventually becoming afflicted with mental illness or PTSD.